ATSᾹR KAFᾹAH QIRᾹAT AL QUR’AN WA ITQᾹN AL MUFRADᾹT LADA AL THULLᾹB ‘ALA MAHᾹRAT AL QIRᾹAH - Jumarliansyah, Muhammad; Hasanah, Mila; Darmawaty, Ridha; Mubarak, Faisal (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
This study aims to examine the effect of reading Quran ability on reading skills, the effect of vocabulary mastery on reading skills, and the effect of reading Quran ability and vocabulary mastery on reading skills students at the Islamic senior high school Amuntai. This type of research is a survey, and the approach used in this research is quantitative. The population of this study was all students of Class XI majoring in MIA at the Islamic senior high school 1 HSU, the Islamic senior high school 2 HSU, and the Islamic senior high school NIPA RAKHA Amuntai, totaling 240 people, and with the sampling technique 25% of the existing population as many as 60 people. The data collection instrument is documentation. The data analysis technique uses multiple regression analysis. The results of this study showed that the reading Quran ability students were in the medium a value of 53%, the vocabulary mastery students were in the medium a value of 72%, and the reading skills students were in the medium a value of 67%. While the effect of reading Quran ability on reading skills was 66.3% which means that there was an effect between the reading Quran ability on reading skills students. While vocabulary mastery on reading skills was 79.4%, there was an effect. Moreover, the effect of reading Quran ability and vocabulary mastery on reading skills students was 85.9%, which means that there is an effect between the reading Quran ability and vocabulary mastery on reading skills students.Keyword: Reading Quran, Vocabulary Mastery, Reading Skills.